Contributions of artifactual materials to the toxicity of anthropogenic soils and street dusts in a highly urbanized terrain. (December 2019) - Howard, Jeffrey; Weyhrauch, Jonathan; Loriaux, Glenn; Schultz, Brandy; Baskaran, Mark
Abstract: A study was undertaken to test the hypothesis that the presence of fly ash and other artifactual materials (AMs) significantly increases the toxicity of urban soil and street dust. AMs were distinguished as artifacts (artificial particles > 2 mm in size), and particulate artifacts (≤2 mm in size); street dust was the <63 μm fraction of street sediments. Reference artifacts, street dusts, and topsoils representing different land use types in Detroit, Michigan were analyzed for miscellaneous radionuclides, trace elements, magnetic susceptibility (MS), and acetic acid-extractable (leachable) Pb. Background levels were established using native glacial sediments. Street sediments were found to have a roadside provenance, hence street dusts inherited their contamination primarily from local soils. All soils and dusts had radionuclide concentrations similar to background levels, and radiological hazard indices within the safe range. Artifacts, fly ash-impacted soils and street dusts contained elevated concentrations of toxic trace elements, which varied with land use type, but none produced a significant amount of leachable Pb. It is inferred that toxic elements in AMs are not bioavailable because they are occluded within highly insoluble materials. Hence, these results do not support our hypothesis. Rather, AMs contribute to artificially-elevated total concentrations leading to an overestimation of toxicity. MS increased with increasing total concentration, hence proximal sensing can be used to map contamination level, but the weak correlation between total and leachable Pb suggests that such maps do not necessarily indicate the associated biohazard. Home site soils with total Pb concentrations >500 mg kg −1 were sporadically toxic. Thus, these results argue against street dust as the local cause of seasonally elevated blood-Pb levels in children. Lead-bearing home site soil tracked directly indoors to form house dust is an alternative exposure pathway. Graphical abstract: Image 1 Highlights: Street dusts inherited their contamination primarily from local soils. All soils and dusts had radiological hazard indices within the safe range. Comon types of artifacts do not produce toxicity in dusts and soils. Street dust is probably not the source of elevated blood-Pb levels. Abstract : Artifactual materials had minimal adverse impact on the toxicity of urban soils and street dusts.